Serological evidence of African swine fever virus infection in commercial pig herds in Southwest Nigeria (2007)
Sera from pigs were assayed for African swine fever virus (ASFV) antibodies to determine the presence and prevalence of ASFV infection in 28 pig herds in southwest Nigeria during 2006 - 2007. A total of 374 pigs were screened in Lagos, Ogun, Ondo, Osun and Oyo States using the Enzyme Linked Immunosorbent Assay method. Out of the 28 farms, 2 were negative (7.1%) for ASFV antibodies. Thirteen out of 15 small herds (86.7%) and 13 out of 13 (100%) medium and large farms were positive for ASFV antibodies. Seroprevalence ranged from 50% (Ondo), 52.5% (Oyo), 59.8% (Lagos), and 60.7% (Ogun) to 70% (Osun). Seroprevalence was higher within the older stocks - finishers, gilts, sows and boars (77.3%- 96.8%) than in the younger stocks - piglets, weaners, and growers (13.8%-39.7%). In essence, almost all breeder stocks became infected. The overall prevalence rate of 65.2% (244/374) and average prevalence rate of 56.8% per farm were indicative of widespread ASFV infection in pig population in southwest Nigeria. This study shows the persistence of ASFV since its re-introduction into southwest Nigeria in 1997. This highlights the need for improved hygiene and biosecurity measures on pig farms. In conclusion, the need for renewed collaboration between livestock and veterinary extension services providers to implement strategies for ASFV control in southwest Nigeria is stressed.